Nutraceutical based SIRT3 activators as therapeutic targets in Alzheimer's disease. (March 2021) - Govindarajulu, Manoj; Ramesh, Sindhu; Neel, Logan; Fabbrini, Mary; Buabeid, Manal; Fujihashi, Ayaka; Dwyer, Darby; Lynd, Tyler; Shah, Karishma; Mohanakumar, Kochupurackal P.; Smith, Forrest; Moore, Timothy; et al.
Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease, and its incidence is increasing worldwide with increased lifespan. Currently, there is no effective treatment to cure or prevent the progression of AD, which indicates the need to develop novel therapeutic targets and agents. Sirtuins, especially SIRT3, a mitochondrial deacetylase, are NAD-dependent histone deacetylases involved in aging and longevity. Accumulating evidence indicates that SIRT3 dysfunction is strongly associated with pathologies of AD, hence, therapeutic modulation of SIRT3 activity may be a novel application to ameliorate the pathologies of AD. Natural products commonly used in traditional medicine have wide utility and appear to have therapeutic benefits for the treatment of neurodegenerative diseases such as AD. The present review summarizes the currently available natural SIRT3 activators and their potentially neuroprotective molecular mechanisms of action that make them a promising agent in the treatment and management of neurodegenerative diseases such as AD. Highlights: Mitochondrial Sirtuin 3 are NAD-dependent histone deacetylases. SIRT3 are involved in aging and longevity. SIRT3 dysfunction is associated with pathologies of AD. Several SIRT3 activators might offer therapeutic benefits in AD.